Timed Bisimulation and Open Maps - Nielsen, Mogens; Hune, Thomas S. (BRICS Report Series, 1998)
Formal models for real-time systems have been studied intensively over the past decade. Much of the theory of untimed systems has been lifted to real-time settings. One example is the notion of bisimulation applied to timed transition systems, which is studied here within the general categorical framework of open maps. We define a category of timed transition systems, and show how to characterize standard timed bisimulation in terms of spans of open maps with a natural choice of a path category. This allows us to apply general results from the theory of open maps, e.g. the existence of canonical models and characteristic logics. Also, we obtain here an alternative proof of decidability of bisimulation for finite transition systems, and illustrate the use of open maps in finite presentations of bisimulations